2011
DOI: 10.1103/physrevlett.106.217401
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Melting of Antiferromagnetic Order inLa0.5Sr1.5MnO4Measured Using Ultrafast Resonant Soft X-Ray Diffraction

Abstract: We used ultrafast resonant soft x-ray diffraction to probe the picosecond dynamics of spin and orbital order in La(0.5)Sr(1.5)MnO(4) after photoexcitation with a femtosecond pulse of 1.5 eV radiation. Complete melting of antiferromagnetic spin order is evidenced by the disappearance of a (1/4,1/4,1/2) diffraction peak. On the other hand, the (1/4,1/4,0) diffraction peak, reflecting orbital order, is only partially reduced. We interpret the results as evidence of destabilization in the short-range exchange patt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 35 publications
3
97
0
Order By: Relevance
“…The long-lived phase that emerges from the photoexcitation process could be spindisordered or ferromagnetic or a mixture of the two. The results of cluster calculations indicated that both are possible in the presence of unperturbed Jahn-Teller distortions [91].…”
Section: (C) Photomelting Of Antiferromagnetic Ordermentioning
confidence: 98%
See 3 more Smart Citations
“…The long-lived phase that emerges from the photoexcitation process could be spindisordered or ferromagnetic or a mixture of the two. The results of cluster calculations indicated that both are possible in the presence of unperturbed Jahn-Teller distortions [91].…”
Section: (C) Photomelting Of Antiferromagnetic Ordermentioning
confidence: 98%
“…The work at Diamond was extended to higher temporal resolution by operating the synchrotron in a low-α mode which allowed the dynamics to be studied with a resolution of approximately 10 ps [91]. However, to understand the details of photomelting antiferromagnetic order on the femtosecond time scale requires the temporal resolution available only at an X-ray free electron laser (XFEL).…”
Section: (C) Photomelting Of Antiferromagnetic Ordermentioning
confidence: 99%
See 2 more Smart Citations
“…6 On the other hand, photoirradiation may induce non-thermal metastable states or transient phases with optical, magnetic and electric properties distinct from that of the ground states. [7][8][9] Among these light-responsive materials, the ferromagnetic materials have been brought into sharp focus by laser-induced demagnetization since Bigot and coworkers found the ultrafast dropping of magnetization in nickel film following optical pulses in 1996. 6 Until recently, the ultrashort pulses of light are applied to manipulate the ultrafast processes in the antiferromagnets.…”
Section: Introductionmentioning
confidence: 99%